Physical, physiological and chemical changes during storage of two sapodilla cultivars - Morais, Patrícia Lígia Dantas de; Lima, Luiz Carlos de Oliveira; Alves, Ricardo Elesbão; Filgueiras, Heloisa Almeida Cunha; Almeida, Adriano da Silva (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the physical, physiological and chemical changes during storage of two sapodilla cultivars (Manilkara sapota L.). Fruits were picked and evaluated at the physiological maturation point, and stored at temperature of 26±2ºC and 55±5% relative humidity. Respiration activities and ethylene production were daily evaluated, while the loss of mass, firmness, pulp color, total titratable acidity, pH, soluble solids content, total sugar and senescence were determined in the 0, 2, 4, 6, 8, 10 and 12 days of storage. Fruits of BRS-228 cultivar had respiration activities, ethylene production picks and senescence retarded when compared to BRS-227 cultivar. Fruits of BRS-228 maintained larger firmness, soluble solids and total sugar contents and smaller loss of mass than BRS-227. The cultivar BRS-228 presents higher postharvest storage potential than BRS-227.